Where does the community start, and where does it end? Including the seed bank to reassess forest herb layer responses to the environment. (16th January 2017) - Plue, Jan; De Frenne, Pieter; Acharya, Kamal; Brunet, Jörg; Chabrerie, Olivier; Decocq, Guillaume; Diekmann, Martin; Graae, Bente J.; Heinken, Thilo; Hermy, Martin; Kolb, Annette; Lemke, Isgard; et al.
Abstract: Question: Below‐ground processes are key determinants of above‐ground plant population and community dynamics. Still, our understanding of how environmental drivers shape plant communities is mostly based on above‐ground diversity patterns, bypassing below‐ground plant diversity stored in seed banks. As seed banks may shape above‐ground plant communities, we question whether concurrently analysing the above‐ and below‐ground species assemblages may potentially enhance our understanding of community responses to environmental variation. Location: Temperate deciduous forests along a 2000 km latitudinal gradient in NW Europe. Methods: Herb layer, seed bank and local environmental data including soil pH, canopy cover, forest cover continuity and time since last canopy disturbance were collected in 129 temperate deciduous forest plots. We quantified herb layer and seed bank diversity per plot and evaluated how environmental variation structured community diversity in the herb layer, seed bank and the combined herb layer–seed bank community. Results: Seed banks consistently held more plant species than the herb layer. How local plot diversity was partitioned across the herb layer and seed bank was mediated by environmental variation in drivers serving as proxies of light availability. The herb layer and seed bank contained an ever smaller and ever larger share of local diversity, respectively, as both canopy cover and time since last canopy disturbance decreased. Species richness and β‐diversity of the combined herb layer–seed bank community responded distinctly differently compared to the separate assemblages in response to environmental variation in, e.g. forest cover continuity and canopy cover. Conclusions: The seed bank is a below‐ground diversity reservoir of the herbaceous forest community, which interacts with the herb layer, although constrained by environmental variation in e.g. light availability. The herb layer and seed bank co‐exist as a single community by means of the so‐called storage effect, resulting in distinct responses to environmental variation not necessarily recorded in the individual herb layer or seed bank assemblages. Thus, concurrently analysing above‐ and below‐ground diversity will improve our ecological understanding of how understorey plant communities respond to environmental variation. Abstract : May a concurrent analysis of forest herb layer, seed bank and combined herb layer‐seed bank species assemblages enhance our understanding of community responses to environmental variation. We show how the herb layer and seed bank coexist as a single community via the storage effect, resulting in distinct environmental responses not necessarily recorded in individual herb layer or seed bank assemblages.